2012
DOI: 10.1051/0004-6361/201118093
|View full text |Cite
|
Sign up to set email alerts
|

Transverse coronal loop oscillations seen in unprecedented detail by AIA/SDO

Abstract: Aims. Detailed analysis of 11 transverse coronal loop oscillations in three events observed with the Atmospheric Imaging Assembly (AIA) instrument on board the Solar Dynamics Observatory (SDO) spacecraft. Detailed analysis includes analysis of the displacement time series, intensity variations and comparing EUVI and AIA data to estimate the 3D loop geometry. Methods. Time distance images extracted from cuts made perpendicular to the oscillations are obtained. A Gaussian plus background fitting technique is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 45 publications
(68 reference statements)
7
74
2
Order By: Relevance
“…The AIA has seven extreme ultraviolet (EUV) bandpasses (Fe XVIII (94 Å) Nakariakov et al 1999;Aschwanden et al 1999Aschwanden et al , 2002Aschwanden & Schrijver 2011;Wang & Solanki 2004;Hori et al 2005Hori et al , 2007Verwichte et al 2009Verwichte et al , 2010McIntosh et al 2011;Mrozek 2011;White & Verwichte 2012;Wang et al 2012) can be either vertically or horizontally polarised and are interpreted as the magneto-hydrodynamic kink mode (Edwin & Roberts 1983;Nakariakov et al 1999;Goossens et al 2009) observed in the corona as the perturbation of the axis of density enhanced loops. To date, there have been few observations of TLOs displaying higher harmonics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AIA has seven extreme ultraviolet (EUV) bandpasses (Fe XVIII (94 Å) Nakariakov et al 1999;Aschwanden et al 1999Aschwanden et al , 2002Aschwanden & Schrijver 2011;Wang & Solanki 2004;Hori et al 2005Hori et al , 2007Verwichte et al 2009Verwichte et al , 2010McIntosh et al 2011;Mrozek 2011;White & Verwichte 2012;Wang et al 2012) can be either vertically or horizontally polarised and are interpreted as the magneto-hydrodynamic kink mode (Edwin & Roberts 1983;Nakariakov et al 1999;Goossens et al 2009) observed in the corona as the perturbation of the axis of density enhanced loops. To date, there have been few observations of TLOs displaying higher harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…AIA/SDO provides new insights into coronal phenomena by increasing both the time and spatial resolutions. As coronal features such as TLOs are studied in ever greater detail (White & Verwichte 2012), signatures of higher harmonics may become easier to observe. The SDO may also provide further opportunities to study the exact nature of oscillations in hot coronal loops.…”
Section: Introductionmentioning
confidence: 99%
“…For example, standing kink oscillations of coronal loops have been used to infer the coronal magnetic field strength (e.g. Nakariakov et al 1999;Nakariakov & Ofman 2001;White & Verwichte 2012) and it has been demonstrated that seismological inversions are consistent with values obtained by magnetic extrapolation and spectral observations (Verwichte et al 2013a). Magnetohydrodynamic waves might also have a significant role in the processes of coronal heating and solar wind acceleration (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…The dashed lines show the background trend, which is assumed to be a polynomial. For example White & Verwichte (2012) use a third order polynomial for the background, while Aschwanden et al (2002) contains examples of polynomial trends with order 1-6. The solid blue curves represent the fitted oscillation with two spectral components, described below.…”
Section: Fitting Standing Kink Mode Harmonicsmentioning
confidence: 99%
“…Kink oscillations are typically detected as strongly damped transverse displacements of coronal loops following eruptive or flare events detected using EUV imaging instruments. The quality and detail of these observations have improved (e.g Aschwanden & Schrijver 2011;White & Verwichte 2012) following the launch of the Solar Dynamics Observatory (SDO) Atmospheric Imaging Assembly (AIA; Lemen et al 2012). More recently, AIA data has been exploited for systematic statistical studies of decaying kink oscillations, which include a catalogue and study of their excitation mechanism (Zimovets & Nakariakov 2015).…”
Section: Introductionmentioning
confidence: 99%